The Application of the Direct Water Cooling Process on the Lost-Foam Casting Technique to Improve Microstructural and Mechanical Properties of A356 Alloy - Tutuk, Ibrahim; Acar, Serhat; Guler, Kerem Altug (SPRINGER INT PUBL AG, 2023)
Lost-foam casting (LFC) is one of the most straightforward techniques to produce complex shaped parts with intricate geometries. However, obtained microstructures are generally coarse in nature due to the slow solidification process. In a previous study, the application of direct water cooling (DWC) in the LFC was proposed with two different approaches. The microstructural features of the water-cooled specimens were found quite promising. In this study, the effects of the DWC were investigated in terms of cooling behaviors, formation of the microstructural elements, and hardness and tensile properties of the lost-foam cast parts of A356 alloy at two different melting temperatures. Secondary dendrite arm spacing and the distance between eutectic particle values were dramatically decreased by the early-stage application of the DWC. The obtained mechanical values were found to be improved compared to the reference samples of both temperatures in terms of tensile strength, elongation to break, and hardness. In addition, selected specimens were subjected to an aging treatment right after the DWC process. The highest obtained mechanical values were found around to be approximately 195 & PLUSMN; 3.5 MPa ultimate tensile strength, 4.45 & PLUSMN; 0.78% elongation, and 84 & PLUSMN; 1.77 HB in hardness. The partial age hardenability of the produced parts with decent percent elongation values might cut off the dependency on the high energy-consuming solution heat treatment process.
Keywords: A356 alloy; direct water cooling; lost-foam casting; Metallurgy & Metallurgical Engineering